The “Sweetness” of Coffee for Jeme Pagar Alam, South Sumatra - Apriani Sapartiwi; Farida R. Wargadalem (Yupa: Historical Studies Journal, 2025)
Abstract Indonesia, known as an agrarian nation, relies heavily on agriculture as the foundation of its economy and a provider of basic human needs. Among its agricultural subsectors, plantations particularly coffee hold strategic economic, social, and cultural significance. In South Sumatra’s Pagar Alam, situated at the foothills of Mount Dempo, coffee cultivation has long been the cornerstone of the local economy. For the indigenous Jeme Pagar Alam community, coffee represents both livelihood and cultural heritage, reflecting generations of agricultural tradition. Despite its economic contributions, challenges such as limited productivity, poor infrastructure, and restricted market access persist. This study examines the socio-economic impacts of coffee cultivation on the Jeme Pagar Alam people in Dempo Utara District from 1997 to 2023, focusing on production trends, pricing, and cultivation practices to reveal the enduring “sweetness” of coffee in sustaining local life.